Characterization of water treatment-resistant and multidrug-resistant urinary pathogenic Escherichia coli in treated wastewater. (1st September 2020) - Zhi, Shuai; Stothard, Paul; Banting, Graham; Scott, Candis; Huntley, Kristin; Ryu, Kanghee; Otto, Simon; Ashbolt, Nicholas; Checkley, Sylvia; Dong, Tao; Ruecker, Norma J.; Neumann, Norman F.
Abstract: A growing body of evidence has demonstrated that extraintestinal pathogenic E. coli (ExPEC), such as the urinary pathogenic E. coli (UPEC), are common constituents of treated wastewater, and therefore represent a potential public health risk. However, no single virulence gene, or set of virulence genes, can be used to conclusively identify this genetically diverse pathotype. As such we sought to identify and characterize the public health relevance of potential UPEC found in treated sewage/wastewater using a comparative genomics approach. Presumptive wastewater UPEC (W-UPEC) were initially identified by virulence gene screening against 5 virulence genes, and for which isolates containing ≥3 virulence genes were whole genome sequenced (n = 24). Single nucleotide polymorphic (SNP) spanning tree analysis demonstrated that many of these wastewater UPEC (WUPEC) were virtually identical at the core genome (0.4 Mbp) when compared to clinical UPEC (C-UPEC) sequences obtained from NCBI, varying by as little as 1 SNP. Remarkably, at the whole genome level, W-UPEC isolates displayed >96% whole genome similarity to C-UPEC counterparts in NCBI, with one strain demonstrating 99.5% genome similarity to a particular C-UPEC strain. The W-UPEC populations were represented by sequence types (ST) known to be clinically important, including ST131, ST95, ST127 and ST640. Many of the W-UPEC carried the exact same complement of virulence genes as their most closely related C-UPEC strains. For example, O25b-ST131 W-UPEC strains possessed the same 80 virulence genes as their most closely related C-UPEC counterparts. Concerningly, W-UPEC strains also carried a plethora of antibiotic resistance genes, and O25b-ST131strains were designated as extended spectrum beta-lactamase (ESBL) producing E. coli by both genome profiling and phenotypic resistance testing. W-UPEC ST131 strains were found in the effluents of a single treatment plant at different times, as well as different wastewater treatment plants, suggesting a differentially ability to survive wastewater treatment. Indeed, in sewage samples treated with chlorine doses sufficient for inducing a ∼99.99% reduction in total E. coli levels, UPEC represented a significant proportion of the chlorine-resistant population. By contrast, no Shiga toxin-producing E. coli were observed in these chlorinated sewage libraries. Our results suggest that clinically-relevant UPEC exist in treated wastewater effluents and that they appear to be specifically adapted to survive wastewater treatment processes. Graphical abstract: Image 1 Highlights: Urinary pathogenic E. coli (UPEC) appear to be resistant to wastewater treatment. Based on comparative genomics, the UPEC found in treated wastewater are clinically important. Pathogenic UPEC strains, such as ST-131 ESBL, can be frequently found in effluents. UPEC comprise a major portion of the E. coli discharged from wastewater treatment plants. Unlike shigatoxin producing E. coli, UPEC appear adapted to survive wastewater treatment.